2019
DOI: 10.1186/s40001-019-0396-3
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-495 serves as a diagnostic biomarker in patients with sepsis and regulates sepsis-induced inflammation and cardiac dysfunction

Abstract: Background: Sepsis leads to severe inflammatory and cardiac dysfunction. This study aimed to explore the clinical value of miR-495 in sepsis, as well as its role in sepsis-induced inflammation and cardiac dysfunction. Methods: 105 sepsis patients were recruited; receiver operating characteristic (ROC) curve was plotted to assess the diagnostic value of miR-495 in sepsis. A model of sepsis in rats was created via performing cecal ligation and puncture (CLP). After modeling, the cardiac function, including left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…As previously described, rats were subjected to CLP to induce sepsis condition. Consistent with the previous study, cardiac function of rats was impaired after CLP (Guo et al, 2019). Moreover, after the knockdown of miR-451a, the impaired cardiac function in sepsis rats, which evidenced by serum cardiac function biomarkers and hemodynamic index, was significantly improved.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As previously described, rats were subjected to CLP to induce sepsis condition. Consistent with the previous study, cardiac function of rats was impaired after CLP (Guo et al, 2019). Moreover, after the knockdown of miR-451a, the impaired cardiac function in sepsis rats, which evidenced by serum cardiac function biomarkers and hemodynamic index, was significantly improved.…”
Section: Discussionsupporting
confidence: 90%
“…The abnormal expression of miRNAs has been reported to be involved in the regulation of inflammatory response in several human disease, including sepsis. For example, miR-495 has been identified to be downregulated in the serum of sepsis patients, and the in vitro study further confirmed that overexpression of miR-495 can alleviate CLP induced inflammatory response (Guo et al, 2019). In the present study, we found that the enhanced inflammatory response was remarkably reversed by the reduction of miR-451a in our constructed septic rat model, as shown by the decreases in pro-inflammatory cytokine levels.…”
Section: Discussionsupporting
confidence: 80%
“…miRNAs can be easily detected from serum and plasma samples, making them a group of good diagnostic tools in various diseases [27]. Guo et al provided evidence for the decreased serum miR-495 as a diagnostic biomarker to screen sepsis patients from healthy population [28]. Lan et al reported that serum miR-155-5p and miR-133a-3p levels were increased in sepsis and related with disease severity, which served as candidate biomarkers for the diagnosis of sepsis [11].…”
mentioning
confidence: 99%
“…MiR-495 was found to be down-regulated in blood samples of septic patients by Guo et al [ 65 ]. Furthermore, it was more decreased in patients who developed septic shock.…”
Section: Resultsmentioning
confidence: 99%